2020
DOI: 10.15761/cogrm.1000299
|View full text |Cite
|
Sign up to set email alerts
|

Three–port robotically assisted laparoscopic hysterectomy (RALH) in case of severe adhesions: A didactic video

Abstract: Post cesarean adhesiolysis during hysterectomy may be sometimes challenging, especially in case of associated adenomyosis or endometriosis. Nowadays, more and more surgeons use robotic assistance to perform laparoscopic hysterectomy. The number and size of trocars may influence postoperative pain. We present in a video a robotically assisted laparoscopic hysterectomy (RALH) using only two instruments and trocars to perform a difficult post cesarean adhesiolysis with removal of associated endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A previous study reported the safety and feasibility of the three-port robot-assisted hysterectomy technique [18]. This technique consists of three 8-mm trocars: one port on the umbilicus for a 0° or 30° optic and two lateral 8-mm ports for the instruments [18,19]. A 30° optic can be useful in cases that allow access to uterine arteries and vesicovaginal fold or culdotomy in some cases with large uteri.…”
Section: Three-port Robotic Hysterectomymentioning
confidence: 99%
“…A previous study reported the safety and feasibility of the three-port robot-assisted hysterectomy technique [18]. This technique consists of three 8-mm trocars: one port on the umbilicus for a 0° or 30° optic and two lateral 8-mm ports for the instruments [18,19]. A 30° optic can be useful in cases that allow access to uterine arteries and vesicovaginal fold or culdotomy in some cases with large uteri.…”
Section: Three-port Robotic Hysterectomymentioning
confidence: 99%